2011
DOI: 10.3349/ymj.2011.52.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Complications after Open Infrarenal Abdominal Aortic Aneurysm Repair in Koreans

Abstract: PurposeOpen infrarenal abdominal aortic aneurysm (AAA) repair is performed without event in most cases. However, some patients suffer major morbidities such as renal failure, myocardial infarction, paraplegia, acute respiratory distress syndrome, or hepatic dysfunction. Predicting what kinds of patient populations are more prone to develop such complications may keep the clinicians more attentive to the patients, possibly leading to better prognoses. In this retrospective study, we searched the incidence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…That vasopressor use and urgent/emergent status are associated with higher risk of mortality is not surprising because they are surrogate markers for patient instability. A number of prior reports on AAA outcomes have similarly reported that both vasopressors 15,16 and acuity 17,18 are associated with high mortality risks. In contrast, octogenarian status as an independent predictor of mortality is relatively novel.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…That vasopressor use and urgent/emergent status are associated with higher risk of mortality is not surprising because they are surrogate markers for patient instability. A number of prior reports on AAA outcomes have similarly reported that both vasopressors 15,16 and acuity 17,18 are associated with high mortality risks. In contrast, octogenarian status as an independent predictor of mortality is relatively novel.…”
Section: Discussionmentioning
confidence: 73%
“…Univariable and multivariable statistics were used to compare perioperative (30-day) and 1-year mortality outcomes between octogenarians vs nonoctogenarians for OAR and EVAR. Results: During the study period, 21,874 patients underwent AAA repair (OAR, 5765; EVAR,16,109), including 4839 octogenarians (OAR, 765; EVAR, 4074) and 17,035 nonoctogenarians (OAR, 5000; EVAR, 12,035). Octogenarians (mean age, 83.0 6 0.1 years) were less frequently male (66% vs 75%) and had a higher prevalence of congestive heart failure (9.9% vs 7.1%), chronic renal insufficiency (12.2% vs 7.5%), and a history of aortic surgery (14.3% vs 7.7%) compared with nonoctogenarians (P < .01 for all).…”
mentioning
confidence: 99%
“…Occlusion and reperfusion of the infrarenal abdominal aorta (IAA) occurs in humans during perivascular surgery [1] and when applied in experimental animal models [2,3]. This method is known to cause ischemia–reperfusion injury (IRI) in various distant organs, such as the kidney, heart, and lungs, which may lead to multiple organ dysfunction syndrome (MODS).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical excision of the affected area and replacement by interposition Dacron grafts is the gold standard for treatment if the dilatation of the aorta exceeds 0.5 cm/year or the ascending aorta is greater than 5 cm in diameter . The conventional surgical approach carries the risks of bleeding, infection, stroke and graft failure . While minimally invasive interventions are getting more frequently used in the treatment of AAA , the use of expanding endovascular stent‐grafts is more limited in ascending AAs due to the presence of branching vessels in the aortic arch .…”
Section: Clinical Managementmentioning
confidence: 99%